2014
DOI: 10.1074/jbc.c113.532267
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Double-stranded Genomic DNA Spanning All Chromosomes with Mutated KRAS and p53 DNA in the Serum Exosomes of Patients with Pancreatic Cancer

Abstract: Background: Exosomes are small vesicles in the tumor microenvironment containing nucleic acids and proteins with the capacity to influence cell behavior. Results: Exosomes contain double-stranded genomic DNA. Conclusion: Exosomes have the capacity to carry and transport genomic DNA spanning all chromosomes with KRAS and p53 mutations. Significance: Exosomes can aid in identifying genomic mutations in patients with pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
767
4
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 859 publications
(804 citation statements)
references
References 23 publications
(31 reference statements)
29
767
4
4
Order By: Relevance
“…The disparity could be related to a different cellular source, or to the diversity of vesiculation processes involved in various systems. However, the ability of cancer cells to emit double-stranded DNA is consistent with several recent observations [18][19][20][21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The disparity could be related to a different cellular source, or to the diversity of vesiculation processes involved in various systems. However, the ability of cancer cells to emit double-stranded DNA is consistent with several recent observations [18][19][20][21].…”
Section: Discussionsupporting
confidence: 91%
“…While the CNV plot suggests some increase in contribution of certain loci (chromosome 11 -upward shift), we have not detected any genomic regions that would be selectively included in EVs (Fig. 3C), as suggested earlier by us [18] and others [20]. Indeed, over 90% of the cellular genome was found in EVs with at least 3 times the coverage of sequences (Fig.…”
Section: Dna Contained In Extracellular Vesicles Represents the Entirsupporting
confidence: 77%
See 2 more Smart Citations
“…Additional studies indicated that the release of small EVs (S-EVs) containing gDNA is driven by specific oncogenes, which are functionally transferred to target cells via EVs [16]. Later reports discovered that exosomes (Exo) contain entire genomes with large fragments (<10,000 bp [base pair]) of dsDNA and carry mutations of parental tumour cells [11,17,18]. These data suggest diagnostic and prognostic value for EV DNA.…”
Section: Introductionmentioning
confidence: 99%